2022
DOI: 10.1108/lhtn-01-2022-0015
|View full text |Cite
|
Sign up to set email alerts
|

Translation strategies of Koha for multilingual interface management

Abstract: Purpose The automation of libraries has made a significant difference in the quality of service. All libraries seek to improve the quality of their services, and the library seems to be a frequent target for modernization efforts throughout the globe. Local dialects need specific translations to use library management software. A variety of languages are available to create open-source techniques. The integrated library management system Koha is gaining traction. The Koha software has been translated and made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Many studies conducted in this field including ; An, J., & Sun, J. (2022), Curran, et al (2022), Francisco-Velilla, et al (2022, Ginting (2022), Hrytsanchuk (2022), Jameel (2022), Li, et al (2022), Saha and Mandal (2022), Giroux, et al (2021), Anber and Jameel (2020), Iglikova and Usataya (2019), and Leni and Pattiwael (2019), showed that using the appropriate translation strategy is the key of successful translation and delivering précis and accurate information in a scientific style. This study tries to enrich the Iraqi literature concerning the translation strategies that the EFL students use in translation and the quality of the translation from English into Arabic or vice versa.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Many studies conducted in this field including ; An, J., & Sun, J. (2022), Curran, et al (2022), Francisco-Velilla, et al (2022, Ginting (2022), Hrytsanchuk (2022), Jameel (2022), Li, et al (2022), Saha and Mandal (2022), Giroux, et al (2021), Anber and Jameel (2020), Iglikova and Usataya (2019), and Leni and Pattiwael (2019), showed that using the appropriate translation strategy is the key of successful translation and delivering précis and accurate information in a scientific style. This study tries to enrich the Iraqi literature concerning the translation strategies that the EFL students use in translation and the quality of the translation from English into Arabic or vice versa.…”
Section: Statement Of the Problemmentioning
confidence: 99%